Clinicians' perspectives on the implementation of patient decision aids in the emergency department: A qualitative interview study. Issue 1 (19th January 2022) - Billah, Tausif; Gordon, Lauren; Schoenfeld, Elizabeth M.; Chang, Bernard P.; Hess, Erik P.; Probst, Marc A.
Abstract: Objective: Decision aids (DAs) are tools to facilitate and standardize shared decision making (SDM). Although most emergency clinicians (ECs) perceive SDM appropriate for emergency care, there is limited uptake of DAs in clinical practice. The objective of this study was to explore barriers and facilitators identified by ECs regarding the implementation of DAs in the emergency department (ED). Methods: We conducted a qualitative interview study guided by implementation science frameworks. ECs participated in interviews focused on the implementation of DAs for the disposition of patients with low‐risk chest pain and unexplained syncope in the ED. Interviews were recorded and transcribed verbatim. We then iteratively developed a codebook with directed qualitative content analysis. Results: We approached 25 ECs working in urban New York, of whom 20 agreed to be interviewed (mean age, 41 years; 25% women). The following 6 main barriers were identified: (1) poor DA accessibility, (2) concern for increased medicolegal risk, (3) lack of perceived need for a DA, (4) patient factors including lack of capacity and limited health literacy, (5) skepticism about validity of DAs, and (6) lack of time to use DAs. The 6 main facilitators identified were (1) positive attitudes toward SDM, (2) patient access to follow‐up care, (3) potential for improved patient satisfaction, (4) potential for improved risk communication, (5) strategic integration of DAs into the clinical workflow, and (6) institutional support of DAs. Conclusions: ECs identified multiple barriers and facilitators to the implementation of DAs into clinical practice. These findings could guide implementation efforts targeting the uptake of DA use in the ED.